PENGGUNAAN DIKSI DALAM CERITA FANTASI SISWA SMP NEGERI 12 PONTIANAK - Wulandari, Kinanti; Sulissusiawan, Ahadi; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractDictation is the right and harmonious choice of words to express ideas. Mistakes in using diction often occur especially in the writing aspect. Misuse of diction causes the real meaning not conveyed properly. The problem in this study is